Zoonotic Diseases from Poultry - Dale, Elizabeth; Brown, Corrie (Brazilian Journal of Veterinary Pathology, 2013)
A wide variety of zoonotic disease risks exists in poultry. Popularity of backyard and smaller production flocks is increasing, as is public concern about global poultry disease events. This paper discusses several of the more common poultry zoonotic diseases, their prevalence and presentation in both poultry and humans.